Experience in using specific recombinant monoclonal antibodies in comorbid patients with coronavirus infection - S. A. Sokotun; A. I. Simakova; A. O. Mikhailov; N. G. Plekhova (Журнал инфектологии, 2024)
Introduction: against the background of the ongoing incidence of coronavirus infection, the selection of therapy often requires individual approaches, especially in comorbid patients. Despite the emergence of specific prevention methods and new antiviral drugs, there are risk groups for severe disease and high mortality.Target. To evaluate the effectiveness and safety of the use of SARSCoV2 neutralizing antibodies for the treatment of comorbid patients with coronavirus infection.Materials and methods: A retrospective study was conducted to evaluate the clinical efficacy of virusneutralizing antibodies for the treatment of comorbid patients with coronavirus infection who were hospitalized in 2022. A total of 244 patient records (mean age 60.0±14.2 years) with confirmed SARSCoV2 coronavirus infection were analyzed. The first group consisted of patients who received monoclonal virusneutralizing antibodies (monotherapy with Sotrovimab or Regdanvimab, combination therapy with Casirivimab and Imdevimab, or Bamlanivimab and Etesevimab), and the second group consisted of patients without therapy. All patients were comorbid. The most frequently observed nosologies were: hypertension (74.1%), chronic kidney disease (55.2%), malignant neoplasms (31%), 1–3 degree of obesity (22.4%), diabetes mellitus (17.2%), and autoimmune diseases (17.2%). In the comparison groups, the duration of the disease, the area of lung tissue damage, the duration of respiratory support, the percentage of complications, the need to use immunosuppressive therapy, as well as the percentage of fatal outcomes, were assessed.Results: The duration of the disease in patients who received monoclonal virusneutralizing antibodies was 16.0±8.1 days, the area of lung tissue damage was on average 14.9±13.0%, the duration of respiratory support was 2.2±3.1 days, complications of coronavirus infection were noted in 31%, the mortality rate decreased to 1.7%. In patients without therapy with these drugs, complications of the disease were detected 2 times more often – in 64% of cases, the duration of the disease was 20.0±6.1 days, the area of lung tissue damage was on average 21.7±12.1%, and the duration of respiratory support was 8.0±6.1 days. Immunosuppressive therapy was used significantly more often in patients without therapy with antiviral monoclonal antibodies (51.2%) than with it (3.4%). A study of the clinical efficacy of various monoclonal antibodies showed an advantage in using Regdanvimab in comorbid patients, as indicated by the absence of fatal outcomes and a reduction in the duration of the disease to 9.8±4.8 days.Conclusions: Preparations of synthetic recombinant monoclonal neutralizing antibodies to SARSCoV2, provided that they are used in the early stages of the disease, significantly reduce the severity of coronavirus infection, the development of complications and significantly reduce mortality in comorbid patients.